Consistency of adults' earliest memories across two years. Issue 1 (2nd January 2019) - Ece, Berivan; Demiray, Burcu; Gülgöz, Sami
ABSTRACT: The consistency of earliest memories in content, dating, and memory qualities was investigated. A total of 84 (27 males; M age = 24.93, SD = 1.36) adults reported earliest memories, estimated ages, and rated their recollections on memory qualities with a two-year time lag. At Time 2, their original reports at Time 1 were presented and they were asked to report whether the earliest memories they recalled at Time 2 were the same. Fifty-six per cent of the participants reported the same earliest memories and those remembering the same events had earlier memories than those remembering different ones. Although no significant differences were observed in estimated ages on the basis of mean ages, a predating bias of later memories and a tendency to postdate earlier memories were observed on the basis of a 48-month cut-off point. Thus, how the data is analysed is critical in detecting dating biases or errors affecting conclusions and interpretations about the dating consistency of earliest memories. Finally, memory qualities of earliest memories displayed a high level of consistency with a two-year time lag regardless of remembering the same versus different event.